Combination of Ultrasound, Tens, And Quadriceps Setting Exercise In Patients With Bilateral Genu Osteoarthritis - Riani Baiduri Siregar (Pena Cendekia Insani, 2022)
Bilateral genu osteoarthritis is a common degenerative condition in the elderly, characterized by pain and limited knee mobility. This study aims to evaluate the effectiveness of combined modality therapy consisting of ultrasound, Transcutaneous Electrical Nerve Stimulation (TENS), and Quadriceps Setting Exercise in improving knee function and reducing pain in patients with bilateral genu osteoarthritis. This study method used a quasi-experimental approach with a pre-test and post-test design. A total of 30 patients were selected by purposive sampling and divided into two groups: the intervention group receiving combined modality therapy, and the control group receiving standard care. The results showed that combined modality therapy significantly increased quadriceps muscle strength, reduced pain levels, and improved physical function compared to the control group. Therefore, this combination therapy is recommended as an effective alternative in the treatment of bilateral genu osteoarthritis.